Perspective method for reconfigurable intelligent surface design for NOMA transmission: Theoretical study - Kontorovich, V. (Frontiers in Communications and Networks, 2023)
The method (paradigm) presented here was inspired by two basic ideas: the assumption of the MIMO-RIS-NOMA communication channel as a dispersive channel with fading, and the representation of the latter by means of the generalized Kronecker channel model (GKCM), applying the “orthogonalization approach” based on utilization of the “universal” eigen basis in the form of prolate spheroidal wave functions (PSWFs). In other words, the essence of the approach is representing the MIMO-RIS-NOMA channel by means of a finite set of artificially created orthogonal trajectories for wave propagation, which are connected by the coupling matrix (CM) of the RIS. The goal for RIS (through the selection of specific CM elements) is to provide a decoding system for the NOMA users with the required SNR values for each user to guarantee successful decoding processing. A theoretical analysis of this paradigm is presented.